A case of reactivation of chronic Epstein-Barr viral infection, complicated by hepatitis, in a teenager with COVID-19 - A. V. Bitsueva; S. G. Gorbunov; I. A. Nikulina (LLC "Diagnostics and Vaccines", 2022)
The article presents a clinical case of reactivation of chronic Epstein-Barr viral (EBV) infection complicated by the development of hepatitis in a 15-year-old teenager with COVID-19, which is of interest to infectious disease practitioners, pediatricians and other specialists in terms of the clinical course and differential diagnosis of these two viral diseases.It is shown that the reactivation of EBV against the background of the current new coronavirus infection COVID-19, accompanied by an increase in the level of aminotransferases in the blood, leads to a more severe course and prolonged stay of the patient in the hospital, as well as the appointment of additional drug therapy with subsequent rehabilitation measures.